Sortilin Modulates Schwann Cell Signaling and Remak Bundle Regeneration Following Nerve Injury - Ulrichsen, Maj; Gonçalves, Nádia P.; Mohseni, Simin; Hjæresen, Simone; Lisle, Thomas L.; Molgaard, Simon; Madsen, Niels K.; Andersen, Olav M.; Svenningsen, Åsa F.; Glerup, Simon; Nykjær, Anders; Vægter, Christian B. (Frontiers in Cellular Neuroscience, 2022)
Peripheral nerve regeneration relies on the ability of Schwann cells to support the regrowth of damaged axons. Schwann cells re-differentiate when reestablishing contact with the sprouting axons, with large fibers becoming remyelinated and small nociceptive fibers ensheathed and collected into Remak bundles. We have previously described how the receptor sortilin facilitates neurotrophin signaling in peripheral neurons via regulated trafficking of Trk receptors. The aim of the present study is to characterize the effects of sortilin deletion on nerve regeneration following sciatic crush injury. We found that Sort1-/- mice displayed functional motor recovery similar to that of WT mice, with no detectable differences in relation to nerve conduction velocities and morphological aspects of myelinated fibers. In contrast, we found abnormal ensheathment of regenerated C-fibers in injured Sort1-/- mice, demonstrating a role of sortilin for Remak bundle formation following injury. Further studies on Schwann cell signaling pathways showed a significant reduction of MAPK/ERK, RSK and CREB phosphorylation in Sort1-/- Schwann cells after stimulation with neurotrophin-3 (NT-3), while Schwann cell migration and myelination remained unaffected. In conclusion, our results demonstrate that loss of sortilin blunts NT-3 signaling in Schwann cells, which might contribute for the impaired Remak bundle regeneration after sciatic nerve injury.